2015
DOI: 10.1177/1934578x1501000122
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile of the Aerial Parts of Sedum sediforme and Anti-inflammatory Activity of Myricitrin

Abstract: The aim of this study was to investigate the phytochemical profile of the methanol extract of the aerial parts of Sedum sediforme and to identify its secondary metabolites. By means of chromatographic separation and enrichment of compounds, HPLC-ESI-MS, HRMS, 1D-, 2D-NMR and/or comparison with reference compounds, three triterpenes, two sterols, ten flavonoids and twelve phenolic compounds were identified, together with two new compounds, i.e. (2R * , 3R *)-5,7-dihydroxy-2,3-dimethyl-4-chromanone-7-O-ß-D-gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…However, at the concentrations corresponding to the IC 50 value calculated after exposure to the extract obtained of S. senegalensis leaves, only 7 proved to be active, leading to a significant inhibitory effect ( p < 0.01) at 3.89 μg mL −1 (8.68 μM), with 12.4% of inhibition. Our data corroborate previous findings on the inhibitory effects of both flavonols against 5-LOX [34,35]. In fact, not only the main components 1 and 7 have been previously reported as 5-LOX inhibitors, but also other flavonol derivatives identified on the hydroethanolic extract obtained from the leaves of S. senegalensis (Table 1 and Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…However, at the concentrations corresponding to the IC 50 value calculated after exposure to the extract obtained of S. senegalensis leaves, only 7 proved to be active, leading to a significant inhibitory effect ( p < 0.01) at 3.89 μg mL −1 (8.68 μM), with 12.4% of inhibition. Our data corroborate previous findings on the inhibitory effects of both flavonols against 5-LOX [34,35]. In fact, not only the main components 1 and 7 have been previously reported as 5-LOX inhibitors, but also other flavonol derivatives identified on the hydroethanolic extract obtained from the leaves of S. senegalensis (Table 1 and Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…The isolation of the main components as well as compounds that were present uniquely in C. spinosum was achieved by fractionation of the extract using countercurrent chromatography (CCC) in step-gradient elution mode. Gradient elution was chosen as an established and most effective method that has been successfully applied for the direct separation of compounds with a wide range of polarities from complex plant extracts [28][29][30]. In order to select a biphasic solvent system for efficient separation, we studied the partition behavior of the main components of the extract (cichoric and caftaric acid) in two simple binary systems: one of medium polarity composed of ethyl acetate: water in a ratio of 1 : 1 (v/v) and a second one of high polarity composed of n-butanol : water 1 : 1 (v/v).…”
mentioning
confidence: 99%
“…[ 18 ] In previous studies was found that compounds such as pinitol,[ 19 ] coumarin[ 20 ] myricitrin (a flavonoid glycoside) have been reported to have anti-inflammatory effects. [ 21 ] These substances found as secondary metabolites may be involved in anti-inflammatory mechanisms.…”
Section: Resultsmentioning
confidence: 99%